Segregation and intrinsec restrictions on canonic variance components - Ferreira, Dário (2020)
This paper deals with the estimability of variance components, in mixed models, when the dimension of the commutative algebra, spanned by all possible variance-covariance matrices, is greater than the number of linearly independente unknown variance components. As example we present an application to a random three-factor crossed-model.